Juridical Review of Prosecutors’ Professionalism in Handling Digital-Based Criminal Cases in Indonesia - Methodius Kossay (Universitas Sains dan Teknologi Komputer, 2026)
The development of information technology has increased digital-based crimes in Indonesia, including online fraud, data theft, and misuse of electronic transactions. This condition requires prosecutors to possess professionalism that is adaptive to technological developments and electronic evidence systems. This study aims to analyze prosecutors’ professionalism in handling digital-based criminal cases, identify the obstacles faced, and examine efforts to improve the quality of law enforcement officers in the digital era. This research uses an empirical legal research method with a socio-legal approach and applies a descriptive qualitative design. Data were collected through interviews, documentation, and literature studies involving 12 informants consisting of 6 prosecutors, 3 criminal law academics, and 3 information technology practitioners. The results show that prosecutors’ professionalism significantly influences the effectiveness of evidence examination and prosecution in digital criminal cases. The study also found several obstacles, including limited technical capabilities, rapid cybercrime development, and lack of optimal coordination among law enforcement institutions. This research is expected to contribute to the development of digital criminal law studies and the improvement of prosecutors’ professionalism in Indonesia.